PENGARUH KERELASIAN PEMASARAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PADA PT ASRI PANCAWARNA - Yuli Evitha (Jurnal Logistik Indonesia, 2017)
The phenomenon that occurs today is the dissatisfaction of customers of PT. Asri Pancawarna / APW, became the basis or purpose of this study. This study aims to determine the content of relation (X1) and product quality (X2), either partially or simultaneously to customer satisfaction (Y).In order to achieve the objectives of the study, this study used questionnaire instruments developed and arranged in Likert Scale. The sample in this study was taken with simple random sampling amount of 67. While the data analysis technique is multiple linear regression.The results showed that Marketing Relationship Against Customer Satisfaction, as well as Product Quality of Customer Density Properties. Marketing Relation Variables and Product Quality can cause 98.2% of Customer Satisfaction.